A Genetic Locus Necessary for Rhamnose Uptake and Catabolism in Rhizobium leguminosarum bv. trifolii - Richardson, Jason S. (American Society for Microbiology, 2004)
Rhizobium leguminosarum bv. trifolii mutants unable to catabolize the methyl-pentose rhamnose are unable to compete effectively for nodule occupancy. In this work we show that the locus responsible for the transport and catabolism of rhamnose spans 10,959 bp. Mutations in this region were generated by transposon mutagenesis, and representative mutants were characterized. The locus contains genes coding for an ABC-type transporter, a putative dehydrogenase, a probable isomerase, and a sugar kinase necessary for the transport and subsequent catabolism of rhamnose. The regulation of these genes, which are inducible by rhamnose, is carried out in part by a DeoR-type negative regulator (RhaR) that is encoded within the same transcript as the ABC-type transporter but is separated from the structural genes encoding the transporter by a terminator-like sequence. RNA dot blot analysis demonstrated that this terminator-like sequence is correlated with transcript attenuation only under noninducing conditions. Transport assays utilizing tritiated rhamnose demonstrated that uptake of rhamnose was inducible and dependent upon the presence of the ABC transporter at this locus. Phenotypic analyses of representative mutants from this locus provide genetic evidence that the catabolism of rhamnose differs from previously described methyl-pentose catabolic pathways.